Innovative dual-gene delivery platform using miR-124 and PD-1 via umbilical cord mesenchymal stem cells and exosome for glioblastoma therapy - Po-Fu Yueh; I-Tsang Chiang; Yueh-Shan Weng; Yu-Chang Liu; Raymond C. B. Wong; Cheng-Yu Chen; Justin Bo-Kai Hsu; Long-Bin Jeng; Woei-Cherng Shyu; Fei-Ting Hsu (Journal of Experimental & Clinical Cancer Research)
Abstract Addressing the challenges of identifying suitable targets and effective delivery strategies is critical in pursuing therapeutic solutions for glioblastoma (GBM). This study focuses on the therapeutic potential of microRNA-124 (miR-124), known for its tumor-suppressing properties, by investigating its ability to target key oncogenic pathways in GBM. The results reveal that CDK4 and CDK6—cyclin-dependent kinases that promote cell cycle progression—are significantly overexpressed in GBM brain samples, underscoring their role in tumor proliferation and identifying them as critical targets for miR-124 intervention. However, delivering miRNA-based therapies remains a major obstacle due to the instability of RNA molecules and the difficulty in achieving targeted, efficient delivery. To address these issues, this research introduces an innovative, non-viral dual-gene delivery platform that utilizes umbilical cord mesenchymal stem cells (UMSCs) and their exosomes to transport miR-124 and programmed cell death protein-1 (PD-1). The efficacy of this dual-gene delivery system was validated using an orthotopic GBM model, which closely mimics the tumor microenvironment seen in patients. Experimental results demonstrate that the UMSC/miR-124-PD-1 complex and its exosomes successfully induce apoptosis in GBM cells, significantly inhibiting tumor growth. Notably, these treatments show minimal cytotoxic effects on normal glial cells, highlighting their safety and selectivity. Moreover, the study highlights the immunomodulatory properties of UMSC/miR-124-PD-1 and its exosomes, enhancing the activation of immune cells such as T cells and dendritic cells, while reducing immunosuppressive cells populations like regulatory T cells and myeloid-derived suppressor cells. The orchestrated dual-gene delivery system by UMSCs and exosomes showcased targeted tumor inhibition and positive immune modulation, emphasizing its potential as a promising therapeutic approach for GBM.